From the Crisis of the Community to the Community of the Crisis. Some Paradoxes of the Being in Common - Pérez Bernal, Ángeles Ma. del Rosario (2013)
This paper explores the idea of community through the proposals of some contemporary thinkers who have tried to rethink the concept of being in common assuming some of its paradoxes. For authors like Roberto Esposito, Jean-Luc Nancy and Giorgio Agamben, thinking “the community” implies reflecting on it from the paradoxes and contradictions it contains, both conceptually and in terms of everyday reality. The central paradox that sums such contradictions is stating that the community is feasible only to the extent that it is not. Close to Russell’s paradox, such aporia allows us to recognize the difference between the community that takes care of its contradictions and inconsistencies, the community of the crisis, and the one that, conceived in absolute and unequivocal terms, is not responsible for their antinomies and contradictions, and leads to what we call the community crisis.